2020
DOI: 10.1021/acsaem.0c01302
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Performance of NaCrO2through Structural Defect Control

Abstract: This study clarifies, for the first time, that misplacement of Cr3+ ions at the Na+ site plays a more important role in dictating the specific capacity and capacity retention over cycles of O3-NaCrO2 cathodes than the Na–O bond length and the NaO2 interlayer spacing do. It is shown that O3-NaCrO2 crystals with a lower degree of misplacement of Cr3+ ions at Na sites and a longer Na–O bond length have higher specific capacity, better capacity retention, and smaller cell impedance. Furthermore, O3-NaCrO2 crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Similar JT distortion is also realized for MnO 6 octahedron in Na 0.93 MnO 2 (Ma et al, 2011), although no detailed structure data was reported. Similarly, no detailed structure data is available for Na x CrO 2 (Luo et al, 2020, Bo et al, 2015. It appears that all these phases have relatively narrow compositionally and thermodynamically stable regions.…”
Section: Occupational Modulation Of Na Atomsmentioning
confidence: 99%
“…Similar JT distortion is also realized for MnO 6 octahedron in Na 0.93 MnO 2 (Ma et al, 2011), although no detailed structure data was reported. Similarly, no detailed structure data is available for Na x CrO 2 (Luo et al, 2020, Bo et al, 2015. It appears that all these phases have relatively narrow compositionally and thermodynamically stable regions.…”
Section: Occupational Modulation Of Na Atomsmentioning
confidence: 99%
“…NaCrO 2 , as a promising cathode material for use in Na-ion batteries (NIBs), has been studied extensively [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. One of the important advantages of NaCrO 2 is its high thermal stability and thus good safety [3].…”
Section: Introductionmentioning
confidence: 99%
“…This irreversible capacity loss has been attributed to the irreversible migration of Cr ions from the octahedral sites in CrO 2 slabs to both tetrahedral and octahedral sites in the Na layer [5,9]. Unfortunately, even for deintercalation of 0.5 moles of Na ions from NaCrO 2 to Na 0.5 CrO 2 , the specific capacity still displays gradual decay over cycles [5,8,[11][12][13][14][15][16][17][18][19], indicating the presence of capacity decay mechanisms even when de/intercalation are between NaCrO 2 and Na 0.5 CrO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors, such as morphology, crystallinity, surface porosity, and defects, are proven and can affect electrochemical properties and HER activity. A defect engineering strategy can increase electrical conductivity and then accelerate the electron transport. Wang and his group concentrated on Co 3 O 4– x bubbles with engineered defects and obtained superior durable hybrid Zn-ion batteries and oxygen evolution/reduction (OER/ORR) reactions.…”
Section: Introductionmentioning
confidence: 99%